Kontekstualisasi Teori Bourdieu dalam Pembentukan Karakter Santri di Pondok Pesantren Darul Falah Amtsilati - Habibi, Najib; Sholikha, Mar'atus (DIMAR: Jurnal Pendidikan Islam, 2025)
This study explores the contextualization of Pierre Bourdieu’s theoretical framework—particularly the concepts of habitus, capital, and field—in the formation of students’ (santri) character within Islamic boarding schools (pesantren) in Indonesia. Amidst the growing discourse on character education and its integration into Islamic institutions, the research addresses the gap in understanding how structural and cultural dimensions influence santri development. The central problem investigated is how Bourdieu’s sociological concepts can be interpreted and applied to strengthen character education in pesantren settings. Employing a qualitative approach with a phenomenological design, the study draws data from observations, interviews, and documentation in selected pesantren. The findings reveal that character formation in santri is significantly shaped by the interaction between religious-cultural values (habitus), the accumulation of religious and social capital, and the power dynamics within the pesantren environment (field). These elements work collectively to internalize discipline, humility, independence, and spiritual resilience among santri. The study offers theoretical contributions by aligning Western sociological theory with local Islamic educational practices and provides practical insights for pesantren leaders to consciously cultivate positive habitus among students. It concludes that Bourdieu’s framework offers a robust lens for analyzing and enhancing character education in pesantren contexts.